Safe Wax Media Bullets for Learning Refuse Bullets - Rahadi, Rahadi (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This innovative work is the result of a modified learning media to reject bullets using bullets made of wax. From the results of the implementation of learning it can be concluded that the use of bullet wax learning media is safe for students, fun and easy to duplicate. From the results of these innovations, it is recommended for physical education teachers who have not carried out bulletproof learning activities because the field conditions are not possible, so they can use wax bullets as a substitute medium, and this has been proven in class VII-C SMP 3 Kediri first semester 2015/2016 in learning to shoot bullets using wax bullets can run safely, smoothly and not damage the environment.